(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2024)
Merremia tridentata (L.) Hallier.f., a member of the Convolvulaceae family, has been traditionally used in various cultures for its medicinal properties. This study investigates the phytochemical composition and antimicrobial activities of M. tridentata leaf extracts obtained using Hexane, Benzene, Acetone, and Water. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and terpenoids. The antimicrobial potential was evaluated using the agar disc diffusion method, where the plant extracts showed significant antibacterial activity against Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus aureus, as well as antifungal effects against Aspergillus niger and Penicillium notatum. These findings support the traditional use of M. tridentata in treating infections and provide a foundation for its further pharmacological development.